PUBLIC SPEAKING ANXIETY AND STRATEGIES TO OVERCOME THROUGH PUBLIC SPEAKING SKILL TRAINING - Thi Thuy Linh, Nguyen; Phan Bao Han, Thai; Minh Son, Tieu; Thi Huyen, Pham (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
Public speaking is recognized as one of the most essential skills in the 21st century, playing a crucial role in assessing students’ speaking abilities and overall communication competence. This is especially important for EFL university students, who face significant challenges in mastering public speaking. This study aims to investigate the causes of public speaking anxiety and examine the effects of workshops on improving students’ public speaking skills. Data were collected through questionnaires with 135 university students in Can Tho city. The findings indicate that the strategies introduced in workshops have a positive impact on students’ public speaking abilities, with fear of negative evaluation identified as the primary source of anxiety. The study also provides pedagogical implications for lecturers and school administrators.